Hopf Cyclicity of a Class of Liénard-Type Systems (Journal of Nonlinear Modeling and Analysis, 2024)
The Hopf cyclicities of some smooth polynomial, rational polynomial and piecewise smooth Liénard systems are studied. For two Liénardsystems with the same damping term and different restoring (or potential)terms, we provide sufficient conditions that the two systems have the sameHopf cyclicity. Then, some examples are given to illustrate the efficiency andapplicability of our results.